Chemical Compounds Isolated from Aerial Part of Primula auriculata L.: Natural compounds from Primula auriculata L - Sahranavard, Shamim; Mojab, Faraz; Naseri, Parya Bolouki; Behzad, Sahar; Khankandi, Hamed Parsa (Iranian Journal of Pharmaceutical Sciences, 2018)
Arial parts of Primula genus (Primulaceae) are well known to treat various ailments in Iranian Traditional Medicine. Our preliminary studies demonstrated that the medium polar to polar extracts of Primula auriculata had a significant cytotoxic activity and Induction of apoptosis effects on some cancerous cell lines. The current study focused on phytochemical investigation and characterization the compounds from P. auriculata active extracts. Dried and powdered aerial part of plant was macerated with petroleum ether, dichloromethane, and methanol successively, for 24 hours, three times. Dichloromethane and methanolic extracts were separately examined by different chromatographic techniques such as VLC, CC, and TLC to Fractionation and isolation compounds present in the plant extracts. The structures of purified compounds were elucidated on the basis of spectral data, particularly H-NMR and C-NMR experiments. 2-phenylchromone and 3, 4, 5-trihydroxy benzoic acid was identified for the first time from P. auriculata. In this research we have isolated compounds from pharmacological active extracts which is most likely responsible for cytotoxic action of P. auriculata. Further studies are required to determine activity and mechanism of action of isolated compounds.